2021
DOI: 10.1186/s12913-021-06525-x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation and pricing of medical services: a policy experiment based in China

Abstract: Background Price regulation is a common constraint in Chinese hospitals. Based on a policy experiment conducted in China on the price deregulation of private nonprofit hospitals, this study empirically examines the impact of medical service price regulation on the pricing of medical services by hospitals. Methods Using the claim data of insured inpatients residing in a major Chinese city for the period 2010–2015, this study constructs a DID (differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We assume that the public hospitals shifted profit sources in this period. On the one hand, the policy of volume-price contracts removed the profit from drug sales, but corresponding compensation through increasing prices for medical services is insufficient ( 31 , 32 ). On the other hand, the policy of volume-price contracts has not been extended to the procurement of consumables in the first reform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the public hospitals shifted profit sources in this period. On the one hand, the policy of volume-price contracts removed the profit from drug sales, but corresponding compensation through increasing prices for medical services is insufficient ( 31 , 32 ). On the other hand, the policy of volume-price contracts has not been extended to the procurement of consumables in the first reform.…”
Section: Discussionmentioning
confidence: 99%
“…Most respondents repeatedly mentioned that compensation for lost revenue by adjusting medical service prices is insufficient and delayed. A long time, the prices of medical service items in public hospitals were adjusted irregularly by the Chinese government ( 31 , 32 ). However, the dynamic and scientific price adjustment mechanism was not established and put into practice, which resulted in the medical service pricing schedules were not updated in timely in most provinces following the pricing reform guidelines ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the proportion of drug fees is also regulated, medical examinations become a staple for hospitals to generate extra revenue, which transfers the burden to the patients who can afford to pay for care [ 26 , 49 ]. A further effect is that this could destroy the medical system’s structure of expenditures [ 50 ]. Consequently, hospitals have a strong incentive to provide excessive medical examinations to gain extra income and lower the proportion of drug fees, leading to increased medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the drug markup policy, the price of the medical service is rigorously controlled by the regulatory authorities, and its value has been underestimated in the last several decades ( 10 ). Wang et al ( 11 ) analyzed the medical service pricing strategies in 30 provinces and found some problems in the charging range, standards, and medical insurance reimbursements.…”
Section: Literature Reviewmentioning
confidence: 99%